Whole-genome analysis reveals a strong positional bias of conserved dMyc-dependent E-boxes. - Hulf, T.; Bellosta, P.; Furrer, M.; Steiger, D.; Svensson, D.; Barbour, A.; Gallant, P. (Molecular and Cellular Biology, 2005)
Myc is a transcription factor with diverse biological effects ranging from the control of cellular proliferation and growth to the induction of apoptosis. Here we present a comprehensive analysis of the transcriptional targets of the sole Myc ortholog in Drosophila melanogaster, dMyc. We show that the genes that are down-regulated in response to dmyc inhibition are largely identical to those that are up-regulated after dMyc overexpression and that many of them play a role in growth control. The promoter regions of these targets are characterized by the presence of the E-box sequence CACGTG, a known dMyc binding site. Surprisingly, a large subgroup of (functionally related) dMyc targets contains a single E-box located within the first 100 nucleotides after the transcription start site. The relevance of this E-box and its position was confirmed by a mutational analysis of a selected dMyc target and by the observation of its evolutionary conservation in a different Drosophila species, Drosophila pseudoobscura. These observations raise the possibility that a subset of Myc targets share a distinct regulatory mechanism.